Career Growth and Joy at Work - Gupta, N.K. (INDIAN EDUCATIONAL REVIEW, 2011)
The present book is about building an enriching and motivating environment around human beings that make one possible to develop strategies around strengths. The book has adapted various concepts of management being practiced in the cooperative word like motivation, creative thinking etc. to individual's concern for career growth and joy while doing work. The book has tried to help individuals visualise and reflect on their strengths and key advantages for working out their unique strategy for career growth. The book has tried to explain an individual's ability to open new avenues for personal growth and career advancement by designing their generic project that may help them in being flexible and responsive to new opportunities. The book begins with describing the basic purpose of work and has differentiated between life and career